DAMPAK LAMA PENGGUNAAN PERANGKAT DIGITAL TERHADAP PROGRESI MIOPIA ANAK - Michellin Purba; Ritsia Anindita; Eva Oktavia; Michael Indra Lesmana (JURNAL KESEHATAN INDRA HUSADA, 2025)
The increasing use of digital devices in children has been associated with the progression of myopia. This literature review aims to analyze the relationship between screen time duration and myopia acceleration in children. The study was conducted by reviewing 12 journals published between 2019 to 2024, using prospective and retrospective observational methods. The results showed that children who spent more than 3-4 hours per day in front of the screen experienced more significant axial elongation and refractive changes than those with lower duration of use. In addition, online learning during the COVID-19 pandemic has been a major factor in the increase in the duration of digital device use, contributing to the accelerated progression of myopia. The literature research involved searching online scientific databases such as Pubmed, Google Scholar, Semantic Scholar and ProQuest. This study emphasizes the importance of reducing screen time and increasing outdoor activities to reduce the risk of myopia in children.